A mini DNA–RNA hybrid origami nanobrick. Issue 14 (11th June 2021) - Zhou, Lifeng; Chandrasekaran, Arun Richard; Yan, Mengwen; Valsangkar, Vibhav A.; Feldblyum, Jeremy I.; Sheng, Jia; Halvorsen, Ken
Abstract : A mini DNA–RNA hybrid origami nanobrick with overall size close to 12 nanometer showed high resistance to nuclease digestion. Abstract : DNA origami is typically used to fold a long single-stranded DNA scaffold into nanostructures with complex geometries using many short DNA staple strands. Integration of RNA into nucleic acid nanostructures is also possible, but has been less studied. In this research, we designed and characterized a hybrid RNA-scaffolded origami nanostructure with dimensions of ∼12 nm. We used 12 DNA staple strands to fold a 401 nt RNA scaffold into a ten-helix bundle with a honeycomb cross section. We verified the construction of the nanostructure using gel electrophoresis and atomic force microscopy. The DNA–RNA hybrid origami showed higher resistance to ribonuclease compared to a DNA–RNA duplex control. Our work shows potential use in folding long RNA, such as messenger RNA, into origami nanostructures that can be delivered into targeted cells as medicine or a vaccine.